Post-pandemic mental health: Psychological distress and burnout syndrome in regular basic education teachers - Estrada Araoz, Edwin Gustavo (2023)
The COVID-19 pandemic has affected the mental health of regular basic education teachers. Despite the fact that in recent months the number of infections has decreased significantly, the return to face-to-face classes is of great concern to teachers due to the adverse educational context they must face. In this sense, the objective of this study was to determine whether or not psychological distress is significantly related to burnout syndrome in regular basic education teachers upon their return to face-to-face classes. This research employed a quantitative approach, the design was nonexperimental, and the type of study was descriptive–correlational and cross-sectional. In total, 184 teachers participated and responded using the Psychological Distress Scale and the Maslach Burnout Inventory, which are instruments with adequate psychometric properties. The results indicated that 40.7% of the teachers had a moderate level of psychological distress, and 45.1% also had a moderate level of burnout syndrome. Likewise, it was found that the Pearson’s r correlation coefficient between the variables psychological distress and burnout syndrome was 0.752, and the p-value was below the level of significance (p < 0.05). It was concluded that there is a direct and significant relationship between psychological distress and burnout syndrome in regular basic education teachers upon their return to face-to-face classes. For this reason, it is suggested that the Ministry of Education should design policies that allow a reassessment of the work that teachers have been carrying out and that promote the implementation of preventive and corrective programs to improve their mental health.